2020
DOI: 10.1007/s10549-020-05724-0
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer care during a pandemic: an opportune time for cryoablation?

Abstract: Purpose Cryoablation is a minimally-invasive percutaneous procedure that is capable of reducing the psychosocial burden of surgical delay while also decreasing the morbidity of breast cancer therapy. The purpose of this editorial is to discuss the potential role of cryoablation for reducing the psychosocial burden of surgical delay during the COVID-19 pandemic by expediting the management of breast cancer while also lessening demand on limited healthcare resources. Methods This editorial critiques current expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 11 publications
0
7
0
2
Order By: Relevance
“…Of the 276,480 new invasive breast cancers expected in 202,0 21 , 70% are expected to be low-risk early-stage (stage I, ERþ, PRþ, and HER2-). 22 With a conservative estimate of half of these tumors being amenable to cryoablation, it would be a feasible option for approximately 100,000 of these patients. This paper documents the initial experience with ultrasoundguided, single-probe cryoablation of early-stage ERþ, PRþ, and HER2-tumors 15 mm without surgical excision with short-term follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 276,480 new invasive breast cancers expected in 202,0 21 , 70% are expected to be low-risk early-stage (stage I, ERþ, PRþ, and HER2-). 22 With a conservative estimate of half of these tumors being amenable to cryoablation, it would be a feasible option for approximately 100,000 of these patients. This paper documents the initial experience with ultrasoundguided, single-probe cryoablation of early-stage ERþ, PRþ, and HER2-tumors 15 mm without surgical excision with short-term follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent editorial, Holmes ( 16 ) suggested that, during the current pandemic, cryoablation therapy could either be a definitive solution or a valid stopgap solution in patients too anxious to delay surgery. Cryoablation has progressively emerged as a minimally invasive new technology alternative to breast cancer surgery, with reduced morbidity and psychosocial and cosmetic impact.…”
Section: Discussionmentioning
confidence: 99%
“…Usando una criosonda de mano similar a una aguja y nitrógeno líquido, los tumores generalmente se ablacionan en dos ciclos de congelación-descongelación que alcanzan una temperatura central de -180°C. Las masas mamarias de menor o igual 2 cm se pueden congelar en tan solo 30-45 min, una lesión cutánea se previene mediante la inyección repetida de solución salina debajo de la dermis para mantener la separación entre la piel y la masa congelada subyacente (Holmes, 2020).…”
Section: Crioablaciónunclassified